Plants vs. zombies. 10, Rumble at Lake Gumbo - Tobin, Paul, 1965- (Dark Horse Books, 2018)
"The battle for clean water begins! As soon as Dr. Zomboss discovers Lake Gumbo near Neighborville, Gargantuars start posing on Muscle Beach, volleyballs bounce off bungee zombies, and Zomboss revs up a giant underwater drill to pollute the lake! Nate, Patrice, and Crazy Dave spot trouble and do all they can to quell another zombie attack"--